Associação entre má-oclusão com alterações fonoarticulatórias e posição de língua em crianças na dentição mista: estudo transversal - Assaf, Débora do Canto (2019)
The aim of this study was to evaluate the association of occlusal alterations with articulation disorders and tongue positioning alterations. This cross-sectional study used a sample of 547 mixed-dentition children aged from 7 to 13 years old from state schools in the city of Santa Maria - RS. The procedure of random sampling by double-stage clustering was adopted, selecting nine schools randomly according to the different administrative regions. The sample was evaluated by questionnaires, dental and phonoaudiological examinations. To verify the risk factors associated with articulation disorders and tongue position alteration, the Poisson regression modeling technique was used. The variables used in the study were: overjet, overbite, posterior crossbite, articulation disorder, tongue position, age, sex, skin color and respiratory mode. Individuals with deep overbite present a protective relationship to articulation disorder, whereas individuals with posterior crossbite are 77% more likely to present this problem. Regarding the change in the position of the tongue, having anterior open bite represents 2.36 times more probability of the individual having this problem. The presence of deep overbite and being male, represent protection factors for alterations in tongue position. On the other hand, have oral/oronasal breathing, represents 2.51 times more frequency of having altered position of the tongue.